Advances in the understanding of the role of degree of saturation and water distribution in mechanical behaviour of calcarenites using magnetic resonance imaging technique. (11th October 2021) - Rabat, Á.; Tomás, R.; Cano, M.
Highlights: MRI revealed that pore water distribution depends on the wetting laboratory process. Water distribution plays a key role in the mechanical behaviour of calcarenites. For low Sr, oven-dried samples usually show smaller strength than immersed samples. For high Sr, mechanical properties are quite similar for both wetting procedures. Important reductions of mechanical properties are obtained when Sr increases. Abstract: A thorough knowledge of the variations of mechanical properties of rock materials with their water content is essential for evaluating the structural behaviour and durability of stone constructions exposed to different moist environments during their lifetime and for solving a broad range of rock mechanics issues. In this study, the effect of degree of saturation (Sr ) and water distribution inside pore network on mechanical parameters such as Uniaxial Compressive Strength, Young's modulus, Brazilian Tensile Strength and Point Load Strength Index was assessed for three varieties of a calcarenite. To this aim, the corresponding mechanical tests and Magnetic Resonance Imaging technique were applied during different time intervals in specimens prepared with different Sr values through two different wetting procedures: (1) the oven drying of saturated samples and (2) the water immersion of dry samples. In general terms, the results showed that for small Sr values (≤50%) the specimens wetted using the drying process exhibit greater mechanical properties reductions than those moistened through the immersion process while for higher Sr values (>50%) the decreases are quite similar for both wetting procedures. As a consequence, different negative exponential functions can be used to describe the relationship between water content and mechanical parameters of calcarenites depending on the wetting procedure used. These results can be explained by the different water distributions inside the partial-saturated specimens and the main involved water-weakening mechanisms. Additionally, slightly different correlation functions between the mechanical parameters were established for specimens moistened using each of the wetting processes.